Continuous Local Antibiotics Perfusion Therapy for Acute Deep Infections after Open Fractures - Shunsuke Takahara; Akihiro Maruo; Hiroyuki Takayama; Toshihiko Harada (Case Reports in Orthopedics)
Unresolved bone and soft tissue infections remain a great hindrance to fracture management worldwide, both economically and functionally for the patient. For this purpose, the benefits of local antibiotic administration besides systemic therapy have been elucidated. We present a retrospective descriptive analysis of six patients (4 males and 2 females) with acute deep infections after open fractures managed using the continuous local antibiotic perfusion (CLAP) therapy. After sufficient debridement, gentamicin solution concentrated at 1,200 μg/mL was continuously infused (2 mL/h) for 7–12 days by syringe pump through an inlet tube placed on the infected area. The antibiotics injected into the infected area were both collected and perfused by negative pressure using a negative-pressure wound therapy system. After an average of 9.5 days of CLAP therapy, symptoms of infection disappeared, and the bacterial culture was negative. There were no cases of recurrence during the follow-up period, and no complications, such as acute renal failure, ototoxicity, allergic or hypersensitivity reactions, and impaired fracture healing, were observed. All six cases were successfully managed with the CLAP therapy without any serious side effects. CLAP therapy may be a potential treatment option for acute deep infections after open fractures.